PUBLIC AND PRIVATE PARTENERSHIP IN INFRASTRUCTURE DEVELOPMENT: ESSENCE, EXPERIENCE, PROBLEMS - Alexander E. Lantsov (Статистика и экономика)
Infrastructure is of high importance for human society, so the state pay great attention to it. Characteristics inherent to infrastructure, its development, maintenance and consumption don’t always explain only the state involvement in the sector.The article considers preconditions and basis of private sector involvement in the process of infrastructure supply, experience of different countries, public and private sectors relationships in the matter and private sector effectiveness in infrastructure supply.